Granisetron vs. granisetron and dexamethasone on the reduction of postoperative nausea and vomiting (PONV) after caesarean section with intrathecal morphine: a randomised controlled trial - Daut, Farah Nasuha Mohd (2021)
Background Intrathecal morphine (ITM) has proven to be excellent in reducing postoperative pain. However, its use is associated with the occurrence of postoperative nausea and vomiting (PONV). In this study, we wish to compare the efficacy between the combination therapy of granisetron and dexamethasone versus granisetron alone on the occurrence of postoperative nausea and vomiting (PONV) in parturients undergoing elective Caesarean delivery. Method This is a prospective double-blinded, randomised controlled trial (RCT) involving 126 parturients of American Society of Anesthesiologist (ASA) physical status I and II undergoing elective Caesarean deliveries. Subjects were randomly allocated into 2 groups (n=63), to either receive a combination of 1mg intravenous (IV) granisetron plus 4mg iv dexamethasone (Group A) or to receive 1mg IV granisetron (Group B). They were assessed at 1, 4, 8, 12 and 24-hour postoperatively. Episodes of nausea, retching, vomiting and the requirement of rescue antiemetics at these time intervals were recorded. Results There are no statistically significant differences in the occurrence of nausea, retching and vomiting between both groups at 1, 4, 8, 12 and 24 hours postoperatively, p=0.999. It was observed that the occurrence of PONV at 1-hour postoperatively was similar between both groups. At 4-hour postoperatively the occurrence of nausea and retching in group A was slightly more than in group B (8.8% vs 7%) but the incidence of vomiting. was similar between both groups (p=0.999). At 8-hour postoperatively, group A recorded a slightly higher occurrence of retching than group B (3.5% vs 1.8%) but then again, this is also statistically insignificant (p=0.999). There was an incident of retching in group B, but there was no episode of PONV seen in patients in group A (1.8% vs 0, p=0.999) at 12-hour post surgery. No episode of PONV were recorded thereafter. It was also found that the usage of rescue antiemetics were similar in both groups of subjects, p=0.999. Conclusion The use of granisetron is comparable with the use of granisetron and dexamethasone in the prevention of PONV in parturients receiving intrathecal morphine for elective Caesarean section.